Marketing Niche Entry Decisions: Competition, Learning, and Strategy in Tokyo Banking, 1894–1936 - Greve, Henrich R. (Academy of Management Journal, 2000)
An organization's choice of a branch location can be analyzed as a market niche entry decision. This study builds theory on how an organization's decision makers evaluate market niches on the basis of competitive environment, learning from others, the organization's own experience, and proactive strategy, and it tests the theory with data on branch entry decisions of early Tokyo banks. Analysis of how decisions were affected by density dependence, mimetic isomorphism, decision-making momentum, and mutual forbearance shows strong evidence of influence from the local competitive environment, the actions of large organizations, and the organization's experience, and weaker evidence of proactive strategy.